STEM-19. RESISTANCE IS FUTILE: UNDERSTANDING AND TARGETING THE CDK5-CREB1-MCL1 AXIS TO PREVENT RADIATION RESISTANCE IN GLIOMA STEM CELLS. (11th November 2019) - Mukherjee, Subhas; Olson, Cheryl; Dunder, Bilge; Sharma, Nitya; Markwell, Steven; Brat, Daniel
Abstract: Glioblastoma is a WHO Grade IV malignant brain tumor with a 95% mortality rate within 2–5 years of diagnosis. This prognosis has not improved in the last 30 years, and with standardized radiation therapy, the cancer always recurs. It is not yet clear why the disease relapses, however recent studies have found that a smaller subset of cells called glioma stem cells (GSCs) are known to be radiation-resistant and cause recurrence of glioblastoma. Thus, to develop precision/personalized cancer medicine that can eliminate GSCs to regress tumor growth and prevent glioblastoma recurrence, it is important to understand the molecular mechanism(s) that causes GSCs to become resistant to radiation therapy. We have found that the atypical protein kinase CDK5 regulates self-renewal in primary GSCs through CREB1. Interestingly, CDK5 inhibition also makes GSCs vulnerable to radiation. Our further investigation revealed that CDK5 may regulate MCL1, an anti-apoptotic BCL2 family protein known to cause radiation resistance. We found that CDK5 regulates MCL1 by directly phosphorylating and stabilizing the protein and also by boosting CREB1 mediated transcription of MCL1. Specific suppression of MCL1 makes GSCs more susceptible to radiation. In collaboration with Dr. Oren Becher, we are generating a new RCAS/tv-a mouse model expressing human MCL1 in tumors to see the accelerated tumorigenicity of MCL1 followed by effectivity of MCL1 suppression in radiation therapy. Thus, in this study, we are aiming to understand and target the unique CDK5-CREB1-MCL1 axis that could be critical for developing therapies to combat glioblastoma radiation resistance.